Al-Takaamul Fii Ta'allumi Qawa'id Al-Lughah Al-Arabiyah Fii Ma'had Insan Qur'ani Bi Aceh Besar - Risna Wardani; Hamid, Abdul; Qomari, Nur (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2022)
Purpose- The purpose of this research is how to integrate in Qawaid Learning at Ma'had Insan Qurani Aceh Besar in learning objectives, teaching materials, teaching methods, and learning evaluations. Design/Methodology/Approach- This research uses a qualitative approach by using the form of a case study. The data sources in this study were the principal, deputy head of the learning section, and Arabic language teachers specifically for qawaid lessons. The data collection techniques used by the researcher were in-depth interviews, observation and documentation. While the instruments used are interview and observation guidelines, data analysis is data reduction (data reduction), data presentation (data display). Findings- The result of the research is that the Qur'anic people have well integrated qawaid learning both in learning objectives, teaching materials, teaching methods, and learning evaluations. Research Limitation/Implications- Researcher has not revealed things related to students' understanding of qawaid learning with an integrative curriculum, therefore researchers and observers of Arabic learning can continue research on various aspects relevant to this research, such as examining the correlation of qawaid understanding with understanding of Arabic reading texts.